A Study on the Prediction of Acid Mine Drainage Formation Rate Using Free Draining Column Leach Test for Acid Mine Drainage Prevention at Laboratory Scale - Jarwinda, Jarwinda; Wibowo, Yudha Gusti; Khanafy, Abdul; Putri, Ilmi Tazkia; Fadillah, M Rizky; Lusitania, Lusitania; Kurniawan, Setyo Budi (Jurnal Sumberdaya Alam dan Lingkungan, 2025)
ABSTRAK Acid Mine Drainage (AMD) is a major environmental concern in coal mining, particularly in Indonesia where surface mining is widely practiced. The exposure of sulfide minerals to water and oxygen leads to the formation of acidic, metal-laden leachate that poses significant risks to water resources, soil quality, and human health. Conventional treatment methods are often expensive and unsustainable, highlighting the need for preventive approaches. This study aims to predict and minimize AMD formation using the Free Draining Column Leach (FDCL) test under simulated wet-dry cycles. Various configurations of Potentially Acid Forming (PAF) and Non-Acid Forming (NAF) materials were tested, with the addition of biochar and zeolite as amendment layers. Static tests, including paste pH, NAG pH, NAPP, and Acid-Base Accounting (ABA), were used to classify the acid-generating potential of the samples. X-ray Diffraction (XRD) was conducted to assess mineral composition, and leachate was analyzed for pH and Total Dissolved Solids (TDS). Results showed that Scheme 3 (PAF–NAF–PAF) had the highest acid generation potential (pH < 4), while Schemes 4 and 5, which included biochar and zeolite, maintained neutral to alkaline conditions and lower TDS. These findings demonstrate the potential of local materials to reduce AMD risks and emphasize the importance of early prevention strategies. The FDCL method offers a valuable tool for improving mine waste management in alignment with sustainable mining practices. Keywords: Acid mine drainage; FDCL test; AMD prediction; biochar; zeolite; mine waste management